KINESIOLOGYCAL ANATOMY ANALYSIS AND BIOMECHANICS OF STRECHING EXERCISES (Fiep Bulletin - online, 2014)
It is related to a field research and bibliographical revision with deepened study of anatomy, kinesiology and biomechanics. It has as an objective to suggest postures and specific angles during the accomplishment of stretching exercises, which are accomplished as part of classes of physical activities and/or supporting in the treatment of several pathologies related to the great articulations of the human body. Initially in a first stage two hundred patients of the Clinic of Physiotherapy of the University Tuiuti of Paraná were observed, in the orthopedics areas, traumatology and sport accomplishing preventive exercises or in treatment. Among the two hundred patients: fifty were feminine sedentary, fifty masculine sedentary, fifty feminine athletes and fifty masculine athletes. They were lifted up all of the stretching exercises that were accomplished inside of a period of sixty days. In a second stage these stretching exercises were studied thoroughly with base in kinesiologycal anatomy and biomechanics. In the third stage, stretching exercises were elaborated with some angles and correct postures, where there was the concern with the prevention of articulate compressions, decrease of tendon and muscular tensions and also with the posture deviations caring with the posture during the EXof the stretching exercises. The skin, muscles, face, ligaments, cartilage and bone answer to great applications of pressure and tension starting from the normal growth and functional hypertrophy or through the physical activity well guided (SMITH et al, 1997). The muscular participation in the stability of an articulation is essential. The antagonist relationship defines the muscular balance gotten by force exercises and of stretching (POCHOLLE & CODINE, 1999). This way, it is justified a study of kinesiologycal anatomy and biomechanics of the stretching exercises presented in this work.
Keywords: stretching; exercise; biomechanics